2005
DOI: 10.1261/rna.2130505
|View full text |Cite
|
Sign up to set email alerts
|

Binding of misacylated tRNAs to the ribosomal A site

Abstract: To test whether the ribosome displays specificity for the esterified amino acid and the tRNA body of an aminoacyl-tRNA (aatRNA), the stabilities of 4 correctly acylated and 12 misacylated tRNAs in the ribosomal A site were determined. By introducing the GAC (valine) anticodon into each tRNA, a constant anticodonÁcodon interaction was maintained, thus removing concern that different anticodonÁcodon strengths might affect the binding of the different aa-tRNAs to the A site. Surprisingly, all 16 aatRNAs displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…As shown in Figure 5, the ΔG° values of the tRNA Phe chimeras correlated closely to the ΔG° values obtained previously for the valylated E. coli tRNAs in nearly identical buffer conditions 6. The difference in the absolute value of ΔG° of the two data sets is primarily accounted for by the fact that tRNAs esterified with valine bind EF-Tu more weakly than the same tRNAs esterified with phenylalanine 19,20. However, the slope of the best fit line for the seven data points is 1.4, suggesting that some aspect of the bodies of several of the tRNAs outside of base pairs 49-65, 50-64, and 51-63 may also contribute to the binding affinity.…”
Section: Resultssupporting
confidence: 83%
“…As shown in Figure 5, the ΔG° values of the tRNA Phe chimeras correlated closely to the ΔG° values obtained previously for the valylated E. coli tRNAs in nearly identical buffer conditions 6. The difference in the absolute value of ΔG° of the two data sets is primarily accounted for by the fact that tRNAs esterified with valine bind EF-Tu more weakly than the same tRNAs esterified with phenylalanine 19,20. However, the slope of the best fit line for the seven data points is 1.4, suggesting that some aspect of the bodies of several of the tRNAs outside of base pairs 49-65, 50-64, and 51-63 may also contribute to the binding affinity.…”
Section: Resultssupporting
confidence: 83%
“…3B), confirming that the ribosome lacks discrimination between Tyr and Phe side chains in the context of tRNA Phe . Previous studies showed that the ribosomal A site has different affinities for various aminoacyl-dinucleotide and puromycin derivatives (Bhuta et al 1981;Starck et al 2003), while nonenzymatic binding experiments suggested that the A site binds all tested misacylated tRNAs and cognate aa-tRNAs uniformly (Fahlman et al 2004;Dale and Uhlenbeck 2005b). Upon codon-anticodon recognition, the ribosome undergoes a series of conformational changes (Pape et al 1998(Pape et al , 1999(Pape et al , 2000Ogle et al 2002;Blanchard et al 2004;Gromadski and Rodnina 2004a,b;Cochella and Green 2005).…”
Section: Misacylation Of Trnamentioning
confidence: 99%
“…Translation inhibition experiments using various puromycin derivatives also indicated that the ribosomal A site specifically recognizes the amino acid side chains of aa-tRNAs (Starck et al 2003). Conversely, nonenzymatic binding studies using full-length aa-tRNAs showed that misacylated and correctly acylated tRNAs bind to the ribosomal A site with similar affinities (Fahlman et al 2004;Dale and Uhlenbeck 2005b). To provide some insights into the discrepancy, we investigated the effect on decoding kinetics of full-length misacylated tRNAs, as part of a broader study of the quality control mechanisms that prevent misincorporation of Tyr at Phe codons.…”
Section: Introductionmentioning
confidence: 99%
“…tRNAs radiolabeled by this protocol have been used to examine many different aspects of protein synthesis. [3'-32 P] tRNAs have been used to examine the interactions between tRNA and modification enzymes [27], the kinetics of tRNA binding to the ribosome [28][29][30][31][32], and the "structure mapping" of tRNAs bound to the ribosome [33].…”
Section: Troubleshootingmentioning
confidence: 99%
“…This assay is especially beneficial for the study of non-natural amino acids since radioactive derivatives are generally not available [10]. Our laboratory has used this method with 13 different aaRSs with either cognate or non-cognate tRNAs [8,30,32] (Ledoux and Uhlenbeck, submitted). Other groups have reported that 15 of the 20 canonical amino acids, as well as pyrolysine, have been esterified to tRNAs using this approach (Table 1) [8,30,[34][35][36][37][39][40][41][42][43][44].…”
Section: Analysis Of Aminoacylated [3'-32 P] Trnasmentioning
confidence: 99%